Medicheck: la plataforma de verificación de noticias médicas - Santolalla Garcia, Gabriel Francisco (2021)
During 2020, there has been an unprecedented change globally. The Covid-19 pandemic has increased media and public opinion's attention on medical subjects related to the virus. This past year we have witnessed a media and social media information overload, where numerous unconfirmed news have been published containing biased and manipulated information. In addition to this, general public wasn't prepared to understand all this information. Fake news are on the rise, misinforming people and giving them fear and suspicion towards medical progress. A good example of this, is the amount of information related to the use of ivermectin that has been published and been exposed in the media, suspected of being fake and manipulated. To battle with this problem, this investigation suggests the creation of an app that allows access verified information regarding covid-19 and it's treatments. This will also allow to debunk certain statements that have appeared on the press on this subject. The main objetive of this project is to generate trust in the population towards medical progress that is being made. Debunking myths and biased statements will also help people to stop self-medicating, because they will have more resources to take care of themselves. With accurate and verified information, a person can make better decisions for their health to battle Covid-19.